School Principal Leadership in Contemporary Education: A Sociological Perspective on Leadership Styles, Challenges, and Implications for Educational Quality - Susi Sabarhati; Siswadi Siswadi; Alifa Muzayyana Putri; Kukuh Jati Winarno (Journal of Innovation and Research in Primary Education, 2026)
School principal leadership constitutes a critical determinant of educational quality, yet comprehensive understanding of effective leadership approaches in contemporary contexts remains limited. This literature review examined school principal leadership from a sociology of education perspective, synthesizing 44 international scholarly sources published between 2019 and 2025. The review employed narrative-descriptive methodology, systematically analyzing leadership conceptualizations, effective styles, contemporary challenges, and implications for educational quality. Findings revealed that 40.9% of contemporary literature conceptualizes principals as multidimensional leaders integrating instructional, managerial, and social roles. Four leadership styles demonstrated differential yet complementary effects: transformational leadership enhanced teacher motivation (85% of studies) and innovation culture (82%); instructional leadership directly improved teaching quality (91%) and curriculum implementation (88%); democratic leadership generated exceptional teacher participation (94%) and organizational trust (87%); while spiritual leadership strengthened ethical climate (89%) and character development (84%). School culture development emerged as the primary mediating mechanism (70.5% of studies) through which leadership influences educational outcomes. Contemporary principals face intensified challenges including digital transformation (77.3%), teacher resistance (63.6%), and administrative burden (59.1%), with significant contextual variations based on resource availability. The findings establish leadership as socially embedded institutional work requiring cultural diagnostic capabilities alongside technical competence. This study advances sociology of education by theorizing principals as cultural producers who shape organizational values mediating educational quality improvements.